Experimental study on the performance of a single-THGEM gas detector - 安正华 吕军光 王志刚 蔡啸 董明义 方建 胡涛 吕绮雯 宁飞鹏 孙丽君 孙希磊 王晓东 薛镇 俞伯祥 章爱武 周莉 郑阳恒 (Chinese physics C, 2010)
A kind of thick GEM-like gaseous electron multiplier （THGEM）, which is mechanically an expansion of the GEM with its various dimensions being enlarged, is studied. The leak current of THGEM plates is measured. The effective gain and energy resolution of a single THGEM are studied with a source of 55Fe, and the effective gain of the single THGEM versus the electric field strength in the induction region is investigated. The results show that the leak current of THGEM plates is less than 200 pA. In an atmospheric-pressure standard gas mixture, 8×103 effective gain and about 32% energy resolution can be reached for the single-THGEM detector.